2009
DOI: 10.1002/qsar.200810050
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Mapping for Kv1.5 Potassium Channel Blockers

Abstract: The ultra-rapid delayed rectifier potassium current (I Kur ), encoded by Kv1.5 gene, is a selective target for the treatment of Atrial Fibrillation (AF). Based on the chemical structures of Kv1.5 potassium channel blockers, a pharmacophore model of Kv1.5 was developed using HypoGen algorithm implemented in Catalyst 4.11 package. The most predictive hypothesis, Hypo1, obtained from 40 training set molecules, consists of one aromatic ring, two hydrophobic points and a hydrogen bond acceptor. This pharmacophore m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In this study, an evaluation of the 3D quantitative structure−activity relationships (QSAR)/PHASE algorithm has been performed for diverse set of hERG blockers. Several studies report the utilization of QSAR methods for studying drug binding to K-channels, including hERG1 blockers. The main idea of QSAR methods is to utilize a general pharmacophore model that can combine information of key functional groups of the ligand and available experimental information on binding for a data set of ligands. A major weakness of approaches based on QSAR is in the alignment and low-resolution of the molecules, as well as a lack of information on protein-drug complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, an evaluation of the 3D quantitative structure−activity relationships (QSAR)/PHASE algorithm has been performed for diverse set of hERG blockers. Several studies report the utilization of QSAR methods for studying drug binding to K-channels, including hERG1 blockers. The main idea of QSAR methods is to utilize a general pharmacophore model that can combine information of key functional groups of the ligand and available experimental information on binding for a data set of ligands. A major weakness of approaches based on QSAR is in the alignment and low-resolution of the molecules, as well as a lack of information on protein-drug complexes.…”
Section: Introductionmentioning
confidence: 99%
“…H ypo G en , the most leading algorithm for the automated pharmacophore generation, was used to identify the critical chemical features of CatD inhibitors. The algorithm has shown to be successful in a large number of applications in medicinal chemistry (38–40). Typically, H ypo G en requires an informative training set as minimum number of 16 molecules with bioactivities spans over four orders of magnitude.…”
Section: Methodsmentioning
confidence: 99%
“…243 In 2002, Ekins et al 244 constructed a 3D-QSAR pharmacophore model for hERG inhibitors based on 22 compounds containing four hydrophobic features and one positive ionization feature. Subsequently, Yang et al 245 developed a pharmacophore model for Kv1.5 based on the chemical structure of a lot of blockers of Kv1.5 channel using the HypoGen method. This pharmacophore model was validated by test set prediction and Fischer randomization tests, and all validation results indicated that it was a statistically good and reliable pharmacophore model.…”
Section: Ligand-based Drug Designmentioning
confidence: 99%